Strategi Pemasaran Berbasis Kualitas Produk, Citra Merek, dan Gaya Hidup: Studi Kasus Keputusan Pembelian Konsumen Mobil Mitsubishi di Kabupaten Kudus - Saputro, Angga Dwi; Utomo, Joko; Supriyono, Supriyono (Journal of Innovation in Management, Accounting and Business, 2024)
Rapid advancements in automotive technology have shifted consumer paradigms regarding four-wheeled motor vehicles, transforming them from mere transportation tools to lifestyle choices. This study investigates the influence of product quality, brand image, and lifestyle on consumer purchasing decisions regarding Mitsubishi automobiles in Kudus Regency. The research methodology employs an explanatory approach, amalgamating qualitative and quantitative data gathered from 125 Mitsubishi consumers.The analysis results reveal significant influences: product quality positively impacts purchase interest and decisions, brand image similarly exerts a significant positive influence on purchase interest and decisions, and lifestyle demonstrates a positive influence on purchase interest and decisions. Purchase interest also functions as a mediating variable between brand image and purchase decisions, as well as between lifestyle and purchase decisions. However, purchase interest does not mediate the relationship between product quality and purchase decisions. In conclusion, product quality, brand image, and lifestyle significantly contribute to the purchasing decisions of Mitsubishi consumers in Kudus Regency, with purchase interest acting as a mediating factor in several relationships. These findings offer crucial insights for manufacturers, marketers, and automotive industry practitioners to develop more effective marketing strategies that cater to consumer needs and attract the market.